Integrating China into multilateral debt relief: Progress and problems in the G20 DSSI - Deborah A. Bräutigam; Yufan Huang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2023)
This paper provides an evaluation of China's participation in the G20's COVID-19 Debt Service Suspension Initiative (DSSI). Through analysis of available data, more than 100 interviews, and fieldwork in Angola, Kenya, and Zambia, we argue, with some caveats, that the DSSI was a success. First, the existing architecture for sovereign debt relief was badly in need of reform. The old system was based on the G7 negotiating rules for relief, which were carried out by the informal Paris Club and the IMF. With the G20 emerging as the premier forum for global economic coordination, and the rise of major new creditors like China and bondholders, new institutions, and new rules, were in order. The DSSI succeeded in providing a pathway for China, the world's largest bilateral creditor, to negotiate debt treatments together with the Paris Club in the context of IMF balance of payments assistance. Getting Chinese commitment to join was 'miraculous' as one G20 participant put it. Yet much remains to be done. Second, China fulfilled its role fairly well as a responsible G20 stakeholder implementing the DSSI in the challenging circumstances of the COVID-19 pandemic. In the 46 countries that participated in the DSSI, Chinese creditors accounted for 30 percent of all claims, and contributed 63 percent of debt service suspensions. The perception that other creditors - private and multilateral banks – were free-riding on Chinese suspensions reinforced Chinese banks' later resistance to providing debt reductions in the Common Framework. On the other hand, Chinese disbursements dropped significantly in countries requesting DSSI relief, but remained steady for other creditors. The terms of the moratorium did not include instructions on how creditors should act in a situation that closely resembled a default. Third, the DSSI prompted China and other G20 creditors to take steps to classify their banks into 'official' and 'commercial' categories, a necessary distinction for member countries participating in the IMF's financing assurances requirement. It pushed the Chinese government to align interests among fragmented banks and bureaucracies with conflicting goals. It started an internal learning process about how debt restructuring has been done historically, and how China might safeguard its interests by participating with others in a multilateral forum. Finally, geopolitical tensions affected negotiations over debt relief and allowed Chinese stakeholders facing losses to argue that pressure from the United States was an effort to "take advantage of China".
Keywords: 330